2015
DOI: 10.3892/or.2015.4275
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNAs involved with hepatocellular carcinoma (Review)

Abstract: Hepatocellular carcinoma (HCC) is one of the most common malignancies, which accounts for 90% of primary liver cancer. HCC usually presents with poor outcomes due to the high rates of tumor recurrence and widespread metastasis. However, the underlying mechanism of HCC initiation and progression, which significantly hindered the development of valid approaches for early detection and treatment remain to be elucidated. As a group of small non-coding RNAs, microRNAs (miRNAs) have been demonstrated to be involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 111 publications
1
53
0
Order By: Relevance
“…It has been reported in multiple studies that miRNAs are involved in the biology of many tumors, playing roles in cell proliferation, differentiation, motility, apoptosis, angiogenesis and metastasis [5-9]. In recent years, many miRNAs have been recognized to promote progression of HCC through enhancing oncogene expression or inhibiting tumor suppressor genes [10-12]. miRNA-873 has been reported to be frequently and aberrantly expressed in many cancers, such as glioblastoma [13], lung adenocarcinoma [14], breast cancer [15] and ovarian cancer [16].…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported in multiple studies that miRNAs are involved in the biology of many tumors, playing roles in cell proliferation, differentiation, motility, apoptosis, angiogenesis and metastasis [5-9]. In recent years, many miRNAs have been recognized to promote progression of HCC through enhancing oncogene expression or inhibiting tumor suppressor genes [10-12]. miRNA-873 has been reported to be frequently and aberrantly expressed in many cancers, such as glioblastoma [13], lung adenocarcinoma [14], breast cancer [15] and ovarian cancer [16].…”
Section: Introductionmentioning
confidence: 99%
“…lncRNAs acting as ceRNAs or natural miRNA sponges are important posttranscriptional regulators of gene expression, which communicate with and coregulate each other by competing for binding to shared miRNAs. Understanding this novel RNA crosstalk will shed light on gene regulatory networks and human development and disease (Afonso‐Grunz & Muller, ; Huarte, ; Mao & Wang, ; Mendell & Olson, ). Here, we showed that lncRNA NORAD overexpressed in HCC tissues, and elevated NORAD positively related to the poor prognosis and high recurrence rate of HCC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, Taraxacum species are found effective against oxidative stress. Recently, it has been reported that T. marginellum was the most efficient extract reducing intracellular ROS levels although in vitro assays, T. obovatum was observed as the best free radical scavenger (Mingarro et al, 2015). Undoubtedly the above studies suggest the promising efficacy of TO against various drugs induced oxidative stress.…”
Section: Antioxidant Effectmentioning
confidence: 91%
“…These strategies are clearly implicated in anticancer efficacy of dandelion. In a very recent study it was found that relevant cytotoxic effect in T. lacistrum extract over HeLa and HepG2 cell lines (Mingarro et al, 2015). However, studies regarding the usefulness of TO against liver carcinoma experimental models are scanty or not available in literature.…”
Section: Anticancer Activitymentioning
confidence: 99%
See 1 more Smart Citation